The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.4172/2168-9881.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Utilization of Insecticide Treated Bed Nets for Malaria Prevention in Ahoada East Local Government Area, Rivers State, Nigeria

Abstract: The study examined the utilization of insecticide treated bed nets for malaria prevention by rural farmers in Ahoada East Local Government Area of Rivers State, Nigeria. The sample size of the study was 100 respondents who were randomly selected from farmers in the area who benefited from the free distribution of the nets by Rivers State Government. The questionnaire was used in eliciting data from the respondents. Data were analyzed with percentage, mean score and multiple regression. Socio-economic result sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The finding implies that relatively older rural farm households prefer ITNs to younger farm households in the rural areas of Akwa Ibom State, Nigeria. The finding was previously substantiated by Nlerum (2016). The marital status of the rural farming household heads indicates that, 9.23% of the rural farm household heads that used ITNs were single, whereas only 2.0% of non-users were single.…”
Section: Results and Discussion Socio-economic Characteristics Of Rur...mentioning
confidence: 64%
See 1 more Smart Citation
“…The finding implies that relatively older rural farm households prefer ITNs to younger farm households in the rural areas of Akwa Ibom State, Nigeria. The finding was previously substantiated by Nlerum (2016). The marital status of the rural farming household heads indicates that, 9.23% of the rural farm household heads that used ITNs were single, whereas only 2.0% of non-users were single.…”
Section: Results and Discussion Socio-economic Characteristics Of Rur...mentioning
confidence: 64%
“…The findings revealed that there was no significant difference in the income of the beneficiaries and non-beneficiaries of the nets. In the southern region of Nigeria, Nlerum (2016) examined the utilization of insecticide-treated bed nets for malaria prevention by rural farmers in Ahoada East Local Government Area of Rivers State. The result revealed an ownership rate of 71.73% and a utilization rate of 28.27%.…”
Section: Introductionmentioning
confidence: 99%